Strategi Penilaian Pembelajaran Daring dengan Penggunaan E-Learning di Masa Pandemi - Fathor Rozi; Faridatul Jannah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to analyze and examine the Online Learning Assessment Strategy Using E-Learning in the Pandemic Period, which was carried out at the University of Nurul Jadid Paiton Probolinggo, in producing a direct picture of the researchers conducted observations and interviews with lecturers, employees, and students of Nurul Jadid University. Methods The research used is a qualitative case study approach. The data analysis technique uses data reduction, data display, and conclusions or verification. The results showed that the lecturer's assessment strategy followed the first discussion forum and presentation, second assignment, third-semester evaluation (exam). This study implies that online learning assessment strategies using e-learning during the pandemic expand access and increase the effectiveness of the learning process; especially during the pandemic, e-learning can also accommodate deficiencies in conventional systems, especially the creation of independent learning.